eIF3 and Its mRNA-Entry-Channel Arm Contribute to the Recruitment of mRNAs With Long 5′-Untranslated Regions - Stanciu, Andrei; Luo, Juncheng; Funes, Lucy; Galbokke Hewage, Shanya; Kulkarni, Shardul D.; Aitken, Colin Echeverría (Frontiers in Molecular Biosciences, 2022)
Translation initiation in eukaryotes is a multi-step pathway and the most regulated phase of translation. Eukaryotic initiation factor 3 (eIF3) is the largest and most complex of the translation initiation factors, and it contributes to events throughout the initiation pathway. In particular, eIF3 appears to play critical roles in mRNA recruitment. More recently, eIF3 has been implicated in driving the selective translation of specific classes of mRNAs. However, unraveling the mechanism of these diverse contributions — and disentangling the roles of the individual subunits of the eIF3 complex — remains challenging. We employed ribosome profiling of budding yeast cells expressing two distinct mutations targeting the eIF3 complex. These mutations either disrupt the entire complex or subunits positioned near the mRNA-entry channel of the ribosome which appear to relocate during or in response to mRNA binding and start-codon recognition. Disruption of either the entire eIF3 complex or specific targeting of these subunits affects mRNAs with long 5’-untranslated regions and whose translation is more dependent on eIF4A, eIF4B, and Ded1 but less dependent on eIF4G, eIF4E, and PABP. Disruption of the entire eIF3 complex further affects mRNAs involved in mitochondrial processes and with structured 5’-untranslated regions. Comparison of the suite of mRNAs most sensitive to both mutations with those uniquely sensitive to disruption of the entire complex sheds new light on the specific roles of individual subunits of the eIF3 complex.